Toxicological evaluation of two children diagnosed as Munchausen syndrome by proxy - Türkmen, Zeynep; Ziyalar, Neylan; Tari, Itır; Mercan, Selda; Kayıran, Sinan Mahir; Şener, Dicle; Cengiz, Salih; Akçakaya, Necla (The Turkish Journal of Pediatrics, 2012)
Munchausen syndrome by proxy is a kind of child abuse in which affected children are often hospitalized for long periods and endure repetitive, painful and expensive diagnostic attempts. We present herein two toxicologically confirmed cases of Munchausen syndrome by proxy. Case 1 is a 16-month-old male who had fever, peripheral cyanosis, tremor, and reported cardiac arrest. Symptoms recurred in the hospital when the mother administered fluids. Toxicology detected 3.5 ng/ml mercury (Hg) in the fluid and 9.4 microg Hg/g creatinine in the urine. Case 2 is a 14-year-old female who had irregular blood findings and multiple hospitalizations. Serum analysis detected warfarin. Both mothers were transferred to psychiatric care. Munchausen syndrome by proxy should be suspected when clinical/laboratory findings are negative, illness descriptions are inconsistent, and frequent hospitalization yields no diagnosis. Psychiatric evaluation and toxicological analysis are recommended.